Formation of the world view of future teachers - Павинська, Н. А. (Scientific notes of the pedagogical department, 2018)
The article deals with the formation of a world outlook for future teachers. Teacher – one of the most important professions of modern society. A modern school needs a teacher capable of adapting and effective activities in the educational environment; to manage the harmonious development of the student’s personality. The author notes that the problem of becoming a worldview of future teachers is conditioned, first of all, by the requirements of modern society to the teacher, his personality characteristics, professional qualities.It is noted that the worldview of the personality of the teacher is considered as a holistic ideal image, which includes the target and cognitive components. A harmonious whole arises from the «ideal whole», that is, the image, «conceptually concentrates in itself the various aspects of life and professional experience, from the angle of view it sets goals». Worldview is a collection of views, ideas, principles of the personality of a specialist in the field of professional activity, which regulate and direct professional activity to achieve the goal.In the course of the study it was established that in the process of formation of a worldview individual’s personality, her beliefs and her life position are formed. It is determined that the worldview is the result and consequence of education and self-education, development and self-development, education and self-education.It was found out that orientation, motives, ideals, knowledge, skills, skills, as well as emotional and volitional personality directly affect the formation of the outlook of future teachers. The formation of the outlook of future teachers takes place through professional knowledge, skills, skills, motives and aspirations, creative orientation, moral and ethical values and settings, as well as cultural and educational potential.The study revealed that the teacher's outlook is regarded as one of the indicators of professional adaptation of a young specialist, and its composition is a collection of gnostic, perceptual-reflexive, constructive, communicative and organizational skills; the structure of which includes a set of various combinations of interactions of creative and professional values, and the concept reflects the dynamics and orientation.